Apoyo emocional de enfermería y ansiedad en paciente prequirúrgico hospital Simón Bolívar Cajamarca - Linares Llico, Rosmery (2023)
The present research entitled "Nursing Emotional Support and Anxiety in Preoperative Patients - Simón Bolívar Hospital Cajamarca" was conducted with a quantitative approach, correlational design, and cross-sectional design to determine if there is a relationship between nursing emotional support and anxiety in preoperative patients. The sample size consisted of 87 patients, with a confidence level of 93.5% and a power of 98%. To assess the level of emotional support, the "Emotional Support Level Questionnaire" developed by Pérez and Ramírez (1997) was used, and to determine the level of anxiety, the "Zung Anxiety Scale" (1965) was applied. The data were processed using the SPSS - 26 statistical package. The results were as follows: 4.6% of patients did not present anxiety, 18.4% had mild anxiety, 50.6% had moderate anxiety, and 26.4% had severe anxiety. 18.4% of patients stated that the level of nursing emotional support was good, 13.8% considered it to be average, and 67.8% considered it to be poor. Furthermore, when evaluating the relationship between the level of emotional support provided by the nursing staff and patient anxiety, a Kendall's tau b value of -0.440 and a Spearman's Rho of -0.613, both with a probability of 0.000, were observed, indicating a highly significant negative relationship between the variables